Fire police: A statutory comparison of the operational nexus between law enforcement and the fire service in six states - Attwood, Wesley R. (International journal of police science & management, 2020)
The disciplines of law enforcement and fire–rescue services have maintained a tradition of performing separately but together in terms of cohesion at the emergency scene. This can be attributed to differing operational focuses and organizational culture, leaving a response gap in unified command and functional response efforts. In order to bridge this cohesion gap, several states have implemented legislation that establishes an operational nexus between the two disciplines. Known as “fire police” in corresponding law, these personnel perform duties that draw upon specialized knowledge and practice in firefighting and police powers. Although these specialized personnel have been used for the past several decades, a void remains in academic discourse of the duties they perform, the powers they maintain for exercise, and where they fit in the emergency response picture. This investigation focuses on fire police within the United States and performs a statutory comparison of the states where they exist to provide a better understanding of their role.